The Azerbaijani Version of History of National Literature: A Critical Review - Mirzoyan, Hrachik; Gonchar, Natalia (Armenian Folia Anglistika, 2012)
The article provides a thorough and detailed examination of the thick collection titled “The Astral Cluster. Folklore and Monuments of Azerbaijan’s Literature” published in Moscow by the publishing house Fiction (Khudozhestvennaya literatura). The authors of the article provide irrefutable evidence to prove that the collection contains numerous and various obvious mistakes, illogical and anti-scientific claims, conscious and unconscious falsifications, explicit aspirations to seize the literary and cultural values of other nations and many other phenomena which are not appropriate for the scientific investigation of the history of culture. And most importantly all this is done with a low language culture. The authors of the article strongly believe that the Azerbaijani scholars showed similar approaches back in the Soviet years. While this is not a new and unexpected incident, it is quite surprising and saddening that all this was allowed in the book published by the famous publishing house Fiction with the support of the Interstate Fund of Humanitarian Co-operation of the CIS member states.